2016
DOI: 10.1371/journal.pone.0158279
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals the Antitumor Mechanism of Polysaccharide from Marine Algae Gracilariopsis lemaneiformis

Abstract: Seaweed is one of the important biomass producers and possesses active metabolites with potential therapeutic effects against tumors. The red alga Gracilariopsis lemaneiformis (Gp. lemaneiformis) possesses antitumor activity, and the polysaccharide of Gp. lemaneiformis (PGL) has been demonstrated to be an ingredient with marked anticancer activity. However, the anticancer mechanism of PGL remains to be elucidated. In this study, we analyzed the inhibitory effect of PGL on the cell growth of 3 human cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…Thus, EVO influenced the expression of genes related to apoptosis and cell cycle. The effects of EVO on Caki-1 cells were similar to those observed for polysaccharides on a non-small cell lung cancer cell line 35 .…”
Section: Discussionsupporting
confidence: 68%
“…Thus, EVO influenced the expression of genes related to apoptosis and cell cycle. The effects of EVO on Caki-1 cells were similar to those observed for polysaccharides on a non-small cell lung cancer cell line 35 .…”
Section: Discussionsupporting
confidence: 68%
“…This confirms the results of previous studies that cembratriene-4, 6-diol has antitumor activity [23]. Thus, the effects of α-CBD on HepG2 and SMMC-7721 cells were similar to those of other substances in a cancer cell line [15,24,25]. The above results showed that the substances with antitumor activity similar to that of α-CBD exert antitumor activity by inhibiting the proliferation of tumor cells.…”
Section: Discussionsupporting
confidence: 90%
“…We previously showed that PGL significantly inhibits lung cancer cell proliferation and changes cell morphology [ 12 ]. Moreover, our transcriptome analysis demonstrated that PGL induced lung cancer apoptosis and cell cycle arrest by modulating the expression of related genes [ 13 ]. In this study, we further investigated PGL antitumor activity in the human gastric cancer cell line MKN28, the lung cancer cell line A549, and the mouse melanoma cell line B16 using CCK-8 assays, phase-contrast microscopy, annexin V-FITC/PI staining, flow cytometry, RT-qPCR, western blotting, and transfections.…”
Section: Introductionmentioning
confidence: 99%